Oral Healthcare Services Delivered During COVID-19 Lockdown: A Report from Eastern Mediterranean Region - Osama Abu-Hammad; Shaden Abu-Hammad; Shadia Elsayed; Safa Jambi; Aishah Alhodhodi; Ahmad Othman; Abdel Aziz Baiomy Abdullah; Hisham Al-Shorman; Mostafa Fayyad; Duaa Taim; Basant Hamdy Abouzaid; Najla Dar-Odeh (Association of Support to Oral Health Research (APESB), 2023)
Objective: To describe oral healthcare services administered during the lockdown in the Eastern Mediterranean region and to investigate the role of socio-professional characteristics of dental practitioners or their self-reported COVID-19 infection. Material and Methods: A questionnaire was distributed to dental practitioners in all healthcare sectors in Jordan, Egypt, and Saudi Arabia. Results: There was a total of 335 participants, with the majority being females (N=225, 67.2%) and general practitioners (N=202, 60.3%). Cellulitis was the most common emergency encountered (N=108). The most common urgent procedures were for pulpitis, abscesses, and pericoronitis (N=191, 130, and 95, respectively). Country-specific significant associations were pulpitis in Egypt and Jordan, broken symptomatic teeth in Jordan, and biopsy in Egypt (p<0.05). The Ministry of Health was significantly associated with the management of dental infections, avulsion, and orthodontic emergencies, while university hospitals were significantly associated with advanced restorative procedures (p<0.05). Male practitioners performed significantly more procedures, particularly surgical emergencies (p<0.05). Conclusion: Dental infections were the most common complaints among dental patients during lockdown. Country- and sector-specific dental procedures are detected. Male gender seems to play a determinant role in performing a higher number of procedures, particularly for surgical emergencies.